2023
DOI: 10.1002/cjoc.202300125
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advance in Low‐Dielectric‐Constant Organosilicon Polymers

Abstract: Comprehensive SummaryLow dielectric (low‐k) organosilicon polymers have received extensive interests from industry and academia due to good electrical insulation, high temperature resistance, flame retardancy and hydrophobicity. These attractive properties enable them to be utilized as low‐k materials in fabrication of electronic devices in high‐frequency communication technology. This review summarizes recent progress in developing low‐k organosilicon polymers, including the synthetic methods and properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 111 publications
0
8
0
Order By: Relevance
“…Lower polarity of polymer backbone has a significant impact on dielectric properties, as poly­(bisS-A) has the highest ε and tan δ among all the hydroxyl-free epoxy thermoplastic samples due to the sulfone groups on its backbone. It is noteworthy that poly­(bisF-A) has a remarkably low ε of 2.26 at 1 MHz, lower than most recently reported hydroxyl-free epoxy resins (Table ), which suggests that the dielectric constant can be reduced by introducing lower polarizable chemical bonds (such as C–F in this structure) on the backbones. The dielectric constant property is the external manifestation of internal microcosmic polarization phenomenon, so the internal polarization mechanism should be discussed. , As Li et al reported that ε generally goes down with increases in the curing degree of thermoset epoxy resin with polarized backbone due to decrease of local mobility, we speculated that lower ε of a linear nonpolar polymer can attribute to a higher degree of freedom of linear polymer chains.…”
Section: Resultsmentioning
confidence: 56%
“…Lower polarity of polymer backbone has a significant impact on dielectric properties, as poly­(bisS-A) has the highest ε and tan δ among all the hydroxyl-free epoxy thermoplastic samples due to the sulfone groups on its backbone. It is noteworthy that poly­(bisF-A) has a remarkably low ε of 2.26 at 1 MHz, lower than most recently reported hydroxyl-free epoxy resins (Table ), which suggests that the dielectric constant can be reduced by introducing lower polarizable chemical bonds (such as C–F in this structure) on the backbones. The dielectric constant property is the external manifestation of internal microcosmic polarization phenomenon, so the internal polarization mechanism should be discussed. , As Li et al reported that ε generally goes down with increases in the curing degree of thermoset epoxy resin with polarized backbone due to decrease of local mobility, we speculated that lower ε of a linear nonpolar polymer can attribute to a higher degree of freedom of linear polymer chains.…”
Section: Resultsmentioning
confidence: 56%
“…The epoxy monomers with low‐molecular polarization and polarized molecular density are synthesized by introducing the low polarizable chemical bonds (such as the CF, 35 CSi, 36 and OSi 37 bonds) or the non‐polar large volume groups (such as the polyhedral oligomeric silsesquioxane [POSS] 38 and adamantane 39 ).…”
Section: Research Process Of Ultra‐low Dielectric Constant Epoxy Resinsmentioning
confidence: 99%
“…Dielectric loss is the phenomenon of energy dissipation in a dielectric material due to changes in an applied electric field. [ 24,25 ] It is typically described by the loss tangent, defined as the ratio of the imaginary part to the real part of the dielectric constant. It is generally represented by the formula(): [ 11 ] tanδ0.33embadbreak=εε0.33em$$\begin{equation}{\mathrm{tan}}\delta \ = \frac{{{\mathrm{\varepsilon ^{\prime\prime}}}}}{{{\mathrm{\varepsilon }}^{\prime}}}\ \end{equation}$$…”
Section: Introductionmentioning
confidence: 99%